1996
DOI: 10.1046/j.1365-2443.1996.d01-237.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative downstream genes of Oct‐3, a pluripotent cell‐specific transcription factor

Abstract: Background: Oct-3, a pluripotent cell-specific POU transcription factor, appears to be a key regulator in pluripotential early embryonic cells and germ cells. In order to study how pluripotency is maintained, it is essential to know what genes are regulated by Oct-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…Oct-3/4 is known to either repress or activate target gene expression [53][54][55][56][57] and regulate the expression of multiple genes downstream [58]. Therefore, the lack of Oct-3/4 expression in SCNT embryos at the later stages of preimplantation development may inhibit their normal development to term.…”
Section: Discussionmentioning
confidence: 99%
“…Oct-3/4 is known to either repress or activate target gene expression [53][54][55][56][57] and regulate the expression of multiple genes downstream [58]. Therefore, the lack of Oct-3/4 expression in SCNT embryos at the later stages of preimplantation development may inhibit their normal development to term.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that LSD1 binds to a proximal enhancer of Lefty1 and regulates Lefty1 expression in mES cells by controlling the methylation status of H3K4 (14,44). Lefty1 encodes a transforming growth factor beta (TGF␤) superfamily protein (45) that antagonizes the functions of Activin and Nodal and is essential in the establishment of left-right asymmetry of the embryo (46,47). It has been suggested that the function of Lefty1 in stem cells is to protect them from the action of developmental inducers (48).…”
Section: ␤-Catenin Chromatin Interactome In Mouse Embryonic Stem Cellsmentioning
confidence: 99%
“…In addition, Oct4 can act on a subset of target genes by binding to alternative A/T-rich sites (Saijoh et al, 1996). Expression of Oct4 occurs in the unfertilized egg and the early embryo prior to segregation of the ICM from the trophectoderm (Pesce and Scholer, 2001).…”
Section: Intrinsic Determinants Of Es Cell Self-renewalmentioning
confidence: 99%